A preliminary evaluation of a new control-knob design for electronic equipment - Andrew, I. D. C.; Ferguson, I.; Talbot, R. J. (College of Aeronautics, 1964)
Two experiments were carried out using five subjects to compare performance using standard and flush fitting rotary controls for electronic equipment. It vas found that the flush knob could be rotated more quickly through several revolutions, but a given setting accuracy was achieved less quickly using this flush knob. Some of the more general advantages and disadvantages of the flush knob are outlined. It should be noted that the primary objective of this study was to provide the participants with some experience in carrying out Human Factors studies and the time allowed was not such as to permit a comprehensive evaluation of the new knob design.